Kajian Mitigasi Bencana Tsunami Berbasis Vegetasi di Pantai Tanjung Aan, Lombok Tengah - Rahayu, Slamet Mardiyanto; Andini, Arista Suci (Fakultas MIPA UNM, 2020)
Abstract.Â Tanjung Aan Beach is one of the beaches in the Mandalika Special Economic Zone (MSEZ), Lombok Island which is prone to tsunami disasters. Moreover, the vegetation on Tanjung Aan Beach has experienced a lot of degradation. Therefore it is necessary to conduct research to determine the types of plants (vegetation) that have the potential to mitigate tsunamis at Tanjung Aan Beach, MSEZ, Central Lombok. The research was conducted with the exploration method (roaming). Based on the research, it can be seen that in Tanjung Aan Beach, Central Lombok there are 3 (types) of plants that have the potential to mitigate the tsunami disaster, namely: Hibiscus tiliaceus, Pandanus utilis, and Terminalia catappa.Keywords:Â mitigation, tanjung aan beach, tsunami, vegetation